Contesting patriotic identities: A study of literary counter-discourse in the advent of the Third Chimurenga - Mhiti, Timothy (University of the Free State, 2020)
This study examines how selected Zimbabwean writers have re-imagined patriotism as a mechanism of re-inventing the nation. It particularly seeks to demonstrate how a literary approach interjects, unsettles, unmakes and re-makes knowledges about contemporary manifestations and (ab)uses of the concept, as well as its historical trajectory and shifts since Zimbabwe’s independence in 1980. The thesis explores literary constructions of national and patriotic identities in the context of the ruling ZANU PF party’s black (neo)nationalist ideological dominance vis-à-vis perceptions of self, agency and the idea of nation, especially in the face of a socio-political and economic crisis that affected Zimbabwe from the year 2000, a period better known as the Third Chimurenga. Therefore, the study is situated within the historically specific temporal and spatial context of the Third Chimurenga where ZANU PF, which has dominated political power since 1980, has propagated grand narratives which authorise a homogeneous vision of the nation and patriotic identities in the Zimbabwean citizenry. The study specifically focusses on contestations between state-sanctioned patriotic identities and counter-discursive imaginaries of patriotism in selected Zimbabwean literary texts. It explores how the literature maps the purported state vision and the counter vision of the nation and engages, at a counter discursive level, with the notion of patriotic identities propagated in the ruling ZANU PF party grand narratives. To this end, the study closely reads novels and short stories by ten different writers, namely Shimmer Chinodya’s “Queues”, Nevanji Madanhire’s “The Grim Reaper’s Car”, Lawrence Hoba’s The Trek and Other Stories, Freedom Nyamubaya’s “That Special Place”, Petina Gappah’s “The President Always Dies in January” and “From a Town called Enkeeldorn”, Christopher Mlalazi’s Running with Mother, Novuyo Rosa Tshuma’s House of Stone, John Eppel’s “The Awards Ceremony”, Diana Charsley’s “The Pencil Test” and Monireh Jassat’s “A Lazy Sunday Afternoon.” The study argues that these texts reflect on different experiences of marginalised patriotisms and contest various forms of exclusion such as political, economic, gender, ethnic and racial in order to counter toxic political processes and debilitating economic circumstances. Thus, the texts’ counter-discursive thrust is broad and an expression of writerly and personal responses to political and economic circumstances birthed by crisis conditions. The study argues that the texts perform various forms of deconstructive acts and each of the texts analysed in this study constitutes a significant archive of the subversion of patriotic identities in post-2000 Zimbabwe. The writers write in idioms of subversion and defiance and evolve and employ multiple textual strategies including exposure, satire, parody, disruption, deconstruction and an engagement in the practice of everyday life to contest the ZANU PF-crafted grand narratives that authorise and prop up patriotic identities. Thus, the study highlights how the texts analysed are at variance with the patriotic history project and construct an alternative vision of the nation and identities, otherwise termed counter-discourses, that is in contradistinction to the patriotic identities that ZANU PF advocates during the Third Chimurenga. The study utilises various strands in postcolonial theory, particularly postcolonial concepts on counter-discourse, notions on identity construction, and ideas on Zimbabwean patriotic identities. Drawing on these concepts, the study explores the deeply political mapping of the idea and memories of the nation and the concept of patriotic identities evident in post-2000 Zimbabwe and contested in the research’s selected texts. The study concludes by noting how these literary interventions are critical in the enunciation of democratic ideals and the suggestion that future research should explore literatures about hegemonic systems and their entrenchment.
Thesis (Ph.D. (English))--University of the Free State, 2020
Keywords: Counter-discourse; Contestation; Nation; Narration; Patriotic identities; Third Chimurenga; Patriotism; Memories; Literary interventions; Zimbabwe - History, 2000-; Zimbabwean literature; Zimbabwean fiction